Effects of Crushed Watermelon Seed on Blood Glucose and Electrolytes Levels in Laboratory Induced Hyperglycaemia - Shingdang, J.*, Okunlola, S., Bot, Y., Ekwempu, A. (Sokoto Journal of Medical Laboratory Science)
Diabetes mellitus a non-communicable disease with a high prevalence globally. It is associated with several complications arising from high blood glucose level (Khaki et al., 2013). This study was carried out to investigate the effects of crushed water melon seed (Citrullus Lanatus) on blood glucose and electrolytes profile of alloxan induced hyperglycaemic Wistar rats. The study design was experimental in nature comprising twenty (20) male Wistar rats grouped into four groups; group 1 (negative control group), group 2 (hyperglycaemic positive control group), group 3 and group 4 were the test groups. The negative control group (group 1) were administered normal rats feed (vital feed) and tap water, Group 2 were made hyperglycaemic by a single dose of intraperitoneal injection of Alloxan monohydrate 180m/kg body weight. Daily crushed water melon seed was administered orally (5g per 100g body weight) mixed with normal rat feed, after 72-hour post Alloxan injection in the test group (group 3 and 4). Fasting blood glucose and electrolyte parameters were determined weekly for a period of four weeks. After the 4th week of treatment, the rats were sacrifice and blood collected via cardiac puncture into lithium heparin tube and plain tubes for electrolyte and blood glucose estimation. The result obtained for basal fasting blood glucose was 3.2mmol/L for group 1 (negative control group), 3.5mmol/L for group 2 (positive control group), 3.0mmol/L for group 3 and 4.0mmol/L for group 4 (test group). After the fourth week of administration of crushed water melon seeds, these values decreased to 3.0 mmol/L. Our work suggests that the glucose concentration decreased significantly (p<0.05) at week 2 and 4 weeks with no significant decrease in electrolyte parameters.  Crushed watermelon seed may be considered as an intervention for hyperglycemic control.